Evaluation of effectiveness of intraoral delivery tip on single step impressions using monophase and two-phase impression materials: An in vivo study - S Gowri; V Shenoy; S Kannan (Wolters Kluwer Medknow Publications, 2015)
Background and Rationale: The precise fit of prosthesis depends on the impression materials and the technique used. Addition silicone impression materials being the user-friendly material are used in monophase and two-phase techniques. Considering the paucity of data on the effectiveness of intraoral delivery tip (IODT) on void, tear and bubble formation using monophase impression technique in stock tray and two-phase impression technique in custom tray the present study was initiated. Materials and Methods: A total of 50 patients requiring single complete veneer crowns were enrolled. Monophase and two-phase impressions with and without IODT were made. Evaluation of the impression were made for tears, voids, and bubbles and alpha, beta, delta scores were given. Results: A significant reduction in the total number of voids was observed with two-phase technique either with or without IODT. No significant differences were observed in the proportion of overall evaluation into alpha, beta and delta between monophase and two-phase with and without IODT. No significant association was seen in the overall evaluation between the two groups (monophase and two-phase) as compared using Chi-square test for independency and a trend in association between overall evaluation as tested using Chi-square for linear trend analysis. Conclusion: Two-phase impression technique with the use of IODT produced decreased number of voids.